Cultural Tourism as a Means of Development of Regional Tourism - Daukaeva Khalida Ibrakhimovna; Mirboboeva Dilfuza Bakhtiyorovna (Universitas Muhammadiyah Sidoarjo, 2020)
There is a significant concentration of cultural attractions in a relatively small territory of Uzbekistan, which together with organized cultural events of various kinds are a prerequisite for the development of cultural tourism in the regions of the country. The current study aims to take an in-depth look at cultural tourism, as well as to indicate the prospects and possible aspects of its future development as a means of development of tourism in regions. To achieve the goal, different approaches to the concept of